Pemanfaatan Inovasi Digital dalam Mempermudah Pembukaan Rekening Masyarakat Secara Online - Trisna, Agung; Niniek Imaningsih (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology has driven significant transformation in the financial sector, including in the process of opening an account online. This community service program aims to improve the digital literacy of the community and assist them in utilizing digital account opening services, especially through the Bank Tabungan Negara (BTN) platform. Activities are carried out through socialization, training, and direct assistance to people who are not yet familiar with digital banking technology. The results of the activities show an increase in the community's understanding and ability to use digital services independently.